In Search of Land and Housing in the New South Africa : The Case of Ethembalethu - Berrisford, Stephen (Washington, DC : World Bank, 2012)
This study analyzes the difficulties a poor community experienced in accessing peri-urban land in South Africa. This community, composed largely of laid-off farm workers, wanted to buy their own farm in a peri-urban area west of Johannesburg to establish a mixed-use settlement. The Ethembalethu 250 families started their own savings scheme to make their dream a reality. Millions of black South Africans live in the peri-urban areas. However, government programs, development planning, and environmental requirements, and the current land and housing markets do not allow them realize their aspirations. Based on this case study, the authors suggest the following areas for policy and program reform: (i) overcoming reluctance and resistance by municipalities and prospective neighbors to low-income settlements; (ii) making land use planning in municipalities explicitly pro-poor; (iii) restructuring the land market; (iv) realigning planning processes; (v) designing a land and housing program targeted to peri-urban areas; (vi) re-engineering program implementations; and (vii) freeing up and building capacity. The study proposes the establishment of a national task force to ensure appropriate follow-up.